The Effect of Different Shelter on The Growth and Survival Rate of Tiger Shrimp Penaeus Monodon Fab. - Dodi Hermawan; Kukuh Nirmala (Jurnal Perikanan dan Kelautan, 2011)
The study on the effect of shelter on growth and survival rate of the tiger shrimp (Penaeun monodon Fab.) have been carried out. Three kinds of different shelters and one control were conducted, namely (1) control, (2) shelter with mangrove branch (3) shelter with coconut branch, (4) shelter with bamboo branch. The result showed that the survival rate of tiger shrimp were 52.00%, 78.67%, 64.00%, 68.00%, respectively, while their growth rate were 9.08%, 7.74%, 5.95%, 6.85%, respectively. These findings indicated that the shelter have affected to the survival rate of the tiger shrimp, however, there were no significant difference in the growth of tiger shrimp.